National policy stakeholder workshop synthesis report - Zimbabwe - Chuma, Edward; Ngoma, Hambulo; Chiduwa, Mazvita S.; Marenya, Paswel (CGIAR, 2023)
Over the past two decades, the world and Africa have seen a change in climatic conditions as a result of climate change, which has resulted in droughts, floods, biodiversity loss and other climate-induced shocks. This, in turn, has impacted agricultural production, further plunging over 400 million people in sub-Saharan Africa in poverty and over 200 million in hunger. The vagaries of climate change have been particularly felt in Zimbabwe, where, on average, the country experiences three drought seasons every five years. The Government of Zimbabwe has taken a policy position to adopt Agroecology and other climate-smart agriculture practices as an adaptation and mitigation strategy to cope with climate change. CIMMYT, a member of the CGIAR research group, has been implementing Agroecology projects in Zimbabwe in districts such as Murehwa and Mbire, recognising stated government-stated policy priorities. A national Agroecology Stakeholder Policy Consultations was convened to analyse the potential for agroecological transition from a policy perspective and to understand how best Agroecology principles can be mainstreamed into policy processes at the national level. The specific objectives were to: • Validate key policies, institutional arrangements, and strategies for agroecological transition and mainstreaming of Agroecology principles (scaling up). • Validate identified key policy stakeholders for agroecological transition and mainstreaming of agroecological principles at the national level informed by specific experiences in Mbire and Murehwa Districts. • Map out a preliminary policy stakeholders’ interest-influence matrix. Identify policy recommendation areas for agroecological transition and mainstreaming of agroecological principles. After an interactive setting-the-scene process, three input presentations were made, followed by a process where workshop participants identified key policies, institutional arrangements, and strategies for agroecological transition and mainstreaming of Agroecology principles (scaling up) in the Zimbabwe context. They also identified all the key policy stakeholders and developed interest-influence stakeholder matrices in three groups. The analysis of the stakeholder matrices resulted in recommendations for managing the stakeholders and for agroecological transition and mainstreaming of agroecological principles.